2011
DOI: 10.1002/14651858.cd008122.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnostic tests for diagnosing uncomplicatedP. falciparummalaria in endemic countries

Abstract: BackgroundRapid diagnostic tests (RDTs) for Plasmodium falciparum malaria use antibodies to detect either HRP-2 antigen or pLDH antigen, and can improve access to diagnostics in developing countries. ObjectivesTo assess the diagnostic accuracy of RDTs for detecting P. falciparum parasitaemia in persons living in endemic areas who present to ambulatory healthcare facilities with symptoms suggestive of malaria by type and brand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
184
2
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 189 publications
(207 citation statements)
references
References 284 publications
17
184
2
4
Order By: Relevance
“…Studies with multiple sites under the same study protocol were pooled directly as one single study in the meta-analysis. With regard to studies that evaluated multiple LED-FM systems on the same group of participants, we included data from only one LED-FM system for the meta-analysis in order to avoid bias caused by counting the same subjects more than once [12]. The LED-FM system most commonly used among our included studies in the meta-analysis was selected to minimise heterogeneity between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with multiple sites under the same study protocol were pooled directly as one single study in the meta-analysis. With regard to studies that evaluated multiple LED-FM systems on the same group of participants, we included data from only one LED-FM system for the meta-analysis in order to avoid bias caused by counting the same subjects more than once [12]. The LED-FM system most commonly used among our included studies in the meta-analysis was selected to minimise heterogeneity between studies.…”
Section: Discussionmentioning
confidence: 99%
“…The development of rapid diagnostic tests (RDTs) has aided diagnosis of malaria in resource-poor settings, but these tests have limited capability for species identification, as they were originally designed to distinguish P. falciparum from other Plasmodium species that cause disease in humans. Numerous studies have demonstrated the utility of RDTs, which have sensitivity and specificity comparable to those of microscopy while offering rapid diagnosis, in Africa and Asia (1,16). The performance of RDTs in areas of low malaria prevalence is less well investigated.…”
Section: T He Accurate Diagnosis Of Malaria By Microscopy In the Unitedmentioning
confidence: 99%
“…1,2 For diagnosing malaria, the microscopic detection of Plasmodium in thick blood films remains the gold standard, although reliable rapid diagnostic tests are increasingly available. 3 In addition, microscopic examination of stained blood films also enables the detection of other pathogens, including Trypanosoma brucei ssp., some of which cause human African trypanosomiasis. Half of all people at risk of African trypanosomiasis live in the Democratic Republic of the Congo, where almost 80% of all reported cases have occurred.…”
Section: Introductionmentioning
confidence: 99%